Assessment of Micro- and Macronutrient Intake in Male Competitive Athletes Using the Epic-Norfolk Food Frequency Questionnaire - Ana Stupin; Leon Perić; Ivana Jukić; Alina Boris; Lorena Stanojević; Ines Drenjančević (Life)
This study aimed to investigate diet quality in a population of male competitive athletes by comparing their total energy and macro- and micronutrients intake assessed by a food frequency questionnaire (FFQ) to current nutritional recommendations for this specific population. An additional goal was to assess athletes’ sodium-to-potassium (Na-to-K) ratio. This cross-sectional study involved 31 healthy competitive male athletes. Subjects’ body mass index, body composition, arterial blood pressure, as well as red blood count (RBC) and serum lipid profile measurements showed that all subjects were lean and normotensive and had normal RBC and serum lipid levels. All subjects completed a cross-culturally adapted, translated, and validated EPIC–Norfolk FFQ. The total energy intake reported in the FFQ was below the recommended values; however, 71% of subjects were classified as low energy reporters (LERs). Energy intake from proteins was within and from carbohydrates was below the recommended interval, while the total energy intake from fats (and also saturated fatty acids) exceeded the recommendations. Suboptimal intakes of vitamin D and folate were observed, indicating the necessity for monitoring (and supplementing) in this population. High Na intake, which despite adequate K intake resulted in a higher Na-to-K ratio, highlighted concerns over excessive salt consumption, but also accentuated the need for monitoring sodium (and potassium) intake in competitive athletes with consideration for sweat-related losses.